PENGAMPUNAN DALAM KITAB NABI-NABI: KAJIAN TEOLOGIS UNTUK GEREJA MASA KINI - Halawa, Iman Kristina; Saut Maruli P. Panggabean (Jurnal Teologi RAI, 2024)
Because of man's fall into sin, the relationship between God and man has been broken. As a result, man needs God's forgiveness. Sin hinders man's relationship with God. Forgiveness, which demonstrates God's loving and gracious nature, is a central theme of Christian theology. In the OT, the concept of forgiveness of sins can be seen from the lives of theprophets who suffered and were persecuted by their people but still provided guidance to others. This research uses a variety of literature research, this research applies a qualitative approach. The purpose of this research is to help modern believers understand how spiritual prophets from the past behaved towards their fellow human beings.   To build harmonious relationships in the midst of conflict and division, forgiveness is important in the contemporary church.   This study emphasises that a deep understanding of forgiveness can help each member of the congregation unite and reconcile while practising tangible deeds of love in daily life.  Therefore, this article assists the theological discussion on forgiveness in the contemporary spiritual and social world.